2022
DOI: 10.1002/ange.202211905
|View full text |Cite
|
Sign up to set email alerts
|

Phase Transitions in Chemically Fueled, Multiphase Complex Coacervate Droplets

Abstract: Membraneless organelles are droplets in the cytosol that are regulated by chemical reactions. Increasing studies suggest that they are internally organized. However, how these subcompartments are regulated remains elusive. Herein, we describe a complex coacervate‐based model composed of two polyanions and a short peptide. With a chemical reaction cycle, we control the affinity of the peptide for the polyelectrolytes leading to distinct regimes inside the phase diagram. We study the transitions from one regime … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…This study represents a significant stride in increasing the degree of complexity of synthetic droplets to emulate cellular features and effectvely integrates recent advances in this field [18, 19, 30, 35, 42, 43]. Notably, while previous research has reported random droplet motion driven by Marangoni flow [27, 5659], it generally relied on the use of surfactants to initiate the Marangoni flow.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…This study represents a significant stride in increasing the degree of complexity of synthetic droplets to emulate cellular features and effectvely integrates recent advances in this field [18, 19, 30, 35, 42, 43]. Notably, while previous research has reported random droplet motion driven by Marangoni flow [27, 5659], it generally relied on the use of surfactants to initiate the Marangoni flow.…”
Section: Discussionmentioning
confidence: 86%
“…The design and control of synthetic droplets able to recall cellular features and respond to chemical signals represent a new frontier for intelligent materials [18][19][20] and biotechnology [21][22][23][24][25][26][27]. In general, synthetic droplets can be obtained either by liquid-liquid phase separation or by encapsulating their content in a membrane (vesicles) [28][29][30][31][32][33][34][35][36][37][38]. Synthetic droplets have been deeply exploited to study cellular features [39][40][41] or to reproduce them [18,[42][43][44].…”
Section: Introductionmentioning
confidence: 99%
“…Some examples of multicompartmentalized coacervate-based structures are proteinosome-in-coacervate, coacervate-in-polymersome, , ATPS-in-liposome, , coacervate-in-liposome, coacervate-in-polymersome, coacervate-in-ATPS, coacervate-in-coacervate, , coacervate-in-hydrogel, , and multiphase coacervates. Some cell functions have been mimicked by these protocells, for example, in the communication between protocells, , between protocells and artificial organelles (AOs), and between AOs within protocells, , as well as cellular processes, such as homeostasis, endocytosis, exocytosis, fusion, division, and gene expression . Therefore, the development of protocells provides some unprecedented advances in the construction of innovative devices with great potential to be used in biomedical applications, such as drug delivery systems, enzyme replacement and gene therapies, and microreactors.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, during germination, etioplasts in plant cells transition from lamellar to nonlamellar membranes upon exposure to light (22,23). Despite previous investigations on the utilization of nonlamellar lipid phases in artificial cells (24)(25)(26)(27)(28)(29)(30)(31), the precise control of phase transitions within these systems remains a significant challenge (32)(33)(34)(35).…”
mentioning
confidence: 99%